The narrative of the epidemic in contemporary travel writing, read in the book "Tindouf'sjourney in the time of Corona" by Abdelkader meski (مجلة إحالات, 2026)
This research paper aims to monitor the narrative of the pandemic in the book "The Tindouf Journeyin the Time of Corona" by Abdelkader Meski, by tracing the textual formats responsible for portraying the impact of the pandemic on Algerian society, because travel literature is a reflective social mirror, an official anthropological document of what happened in history and the emergency and new events taking place, and a pictorial literary art that aspires to an integrated historical consolidation.